ANALISIS PENGARUH TEBAL PELAT WELDING REPAIR PADA KEMUDI KAPAL (RUDDER) TERHADAP EFEKTIVITAS MANUVER KAPAL DENGAN - Fiveriati Anggra; Darma Yonathan Eka Yeddid; Puspasari Vinda (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Ship maneuverability is the ability of the ship to rotate and change direction in all conditions of the water when the rudder (steering) turns to form a certain angle; there is a change in pressure, speed and direction of fluid flow, this causes changes in the course of the ship. Corals that produce the rudder of the vessel to crack or break because of the impact of the rock at that time the rudder needs a repair. Repair on the rudder of the ship is usually carried out on the leaves and sticks of steering, one of the repairs processes is by welding, but if the rudder undergoes a reparation process many times, it will cause changes in metallurgical material due to excessive heat treatment. In the process of repairing the rudder, the new plate used to improve the maximum is 1 mm with an old plate, and the rear side of the rudder experiences a higher load because in this part the flow distribution is stacked from the front of the rudder. The results of this study are repaired rudder experiencing an increase of 16% -18% drag and lift force, the faster the ship runs, the higher the drag and lift force so that the resistance is also greater Keywords: Rudder, Maneuver, Repair